2011
DOI: 10.1016/j.neuroimage.2011.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Occipital gamma-oscillations modulated during eye movement tasks: Simultaneous eye tracking and electrocorticography recording in epileptic patients

Abstract: We determined the spatio-temporal dynamics of cortical gamma-oscillations modulated during eye movement tasks, using simultaneous eye tracking and intracranial electrocorticography (ECoG) recording. Patients with focal epilepsy were instructed to follow a target moving intermittently and unpredictably from one place to another either in an instantaneous or smooth fashion during extraoperative ECoG recording. Target motion elicited augmentation of gamma-oscillations in the lateral, inferior and polar occipital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 38 publications
2
52
1
Order By: Relevance
“…The late onsets of neural activity in MOG and CUN that followed target motion onset, are consistent with a previous report and confirm that occipital activity propagate from lateral to medial occipital sites during pursuit (Nagasawa et al, 2011).…”
Section: Vips and Occipital Areassupporting
confidence: 92%
See 1 more Smart Citation
“…The late onsets of neural activity in MOG and CUN that followed target motion onset, are consistent with a previous report and confirm that occipital activity propagate from lateral to medial occipital sites during pursuit (Nagasawa et al, 2011).…”
Section: Vips and Occipital Areassupporting
confidence: 92%
“…In the pursuit FEF, gamma band activity was higher during RP than during PI, indicative of a role in pursuit maintenance, whereas the saccade FEF was characterized by a transient gamma activity that is consistent with the pattern of gamma activity observed in the two previous FEF direct recordings (Lachaux et al, 2006;Nagasawa et al, 2011). Gamma power was higher during reactive compared to predictive pursuits in saccade FEF, perhaps because during RP, more saccades occurred in this study.…”
Section: Frontal Eye Fieldsupporting
confidence: 87%
“…Other studies performed with electrocorticography described gamma band augmentation during eye movement tasks (Nagasawa et al, 2011); during photic stimuli, a high-gamma augmentation was most prominent in the medial occipital region (Matsuzaki et al, 2012). It is not clear if the evoked gamma activity evaluated by these studies is related to the spontaneous continuous HFA reported in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…The finding of duration-tracking responses could be potentially explained as the temporally summed activity of transient (onset) responses to retinal shifts driven by eye movements (EM) while the stimulus is presented (Nagasawa et al, 2011). However, there are good reasons to suggest that duration-tracking responses are not merely driven by EM.…”
Section: Resultsmentioning
confidence: 99%